Compensated Convex-Based Transforms for Image Processing and Shape Interrogation - Elaine Crooks (Handbook of Mathematical Models and Algorithms in Computer Vision and Imaging, 2023)
This paper reviews some recent applications of the theory of the compensated convex transforms or of the proximity hull as developed by the authors to image processing and shape interrogation with special attention given to the Hausdorff stability and multiscale properties. This paper contains also numerical experiments that demonstrate the performance of our methods compared to the state-of-art ones.